Gamification in the STEM Domain Subject: The Prospective Method to Strengthen Teaching and Learning - Arlinwibowo, J.; Ishartono, N.; Linguistika, Y.; Purwoko, D.; Suprapto, S. (Jurnal Pendidikan IPA Indonesia, 2023)
Several meta-analysis studies related to game-based learning or Gamification have been carried out by various researchers. However, there is still a scarcity of studies specifically elucidating the extent of Gamification's impact on STEM domain subjects. Therefore, this research aims to summarize various research results related to the influence of game-based learning in improving student learning outcomes in STEM domain subjects. This research was a meta-analysis using the standardized group contrast design with a random model. Research data were from articles published in Scopus-indexed journals or proceedings. The inclusion criteria in this research were articles published between 2014 – 2023 in English, quantitative type data with a contrast group design containing control and experimental groups, complete data (n, mean, SD), and research focused on STEM domain subjects. The data collection process used the PRISMA method. To ensure data quality, researchers conducted publication bias analysis using the fail-safe N method. The moderator variables were continent, stem domain, era, developing competency, game type, and education level. The results find that Gamification has a positive impact on student learning outcomes, as indicated by an effect size value of 0.5492 [0.3943; 0.7041] with a confidence interval of 95%. Gamification does not provide a significant positive difference in the moderator variables continent, era, developing competence, and game type. For STEM domain subjects, Gamification is highly recommended to be applied. For the educational level, Gamification is most recommended to be implemented in elementary school.